Exploring differences in work values among multigenerational workforce: Leadership approaches in selected higher educational institutions in the UAE - AL MARZOOQI, LOLOWA (2017)
The present research focuses on exploring work-related values among the multigenerational workforce of the two of the UAE higher educational institutions: Abu Dhabi University and Zayed University. The study is based on a mixed-method approach (a work value inventory-based questionnaire and semi-structured interviews with managers employed by the abovementioned universities), and attempts to better understand values of Millennials, Baby Boomers and Generation X-ers employed within the UAE universities. The study depends on the following guided theories Schwartz theory, Perry general theory, Sagie employee values, Mannheim theory, and Bownen’s family systems, besides most appropriate leadership approaches that can be adopted to avoid any inter-generational conflicts and challenges, as well as develop a sustainable competitive advantage. According to the obtained results, the work values of the UAE Millennials, Baby Boomers and Generation X-ers differ from empirical evidence from the Western countries. The UAE Millennials were demonstrated to highly value job security as opposed to their Western peers, while the UAE Baby Boomers had little regard for economic return of their jobs. When Millennials were compared with Baby Boomers, it was discovered that there were significant differences in all three of the scored values: salary raise (M=3.04 and M=3.28, p=0.011), pay increases to balance cost of living (M=3.05 and M=3.41, p=0.00) and being paid well (M=3.06 and M=3.41, p=0.003). A similar picture was observed when comparing Generation X-ers with Baby Boomers: salary raise (M=2.99 and M=3.28, p=0.00), pay increases to balance cost of living (M=2.99 and M=3.41, p=0.00) and being paid well (M=2.98 and M=3.41, p=0.00). Intrinsic motivation has been demonstrated to be a highly powerful source of motivation for all of the three cohorts, however particularly important for Millennials and Baby Boomers, who had little regard for economic return. According to the present thesis, there are significant differences in work values between the three generations in UAE, which in turn differ from the values of employees from the Western countries. Moreover, the UAE educational leadership has been demonstrated to be lacking regard for multigenerational differences, as well as rigid and hierarchical. Therefore, appropriate leadership approaches based on transformational leadership, fostering workplace diversity and promoting culture of empowerment and inclusion, have to be adopted in order to motivate Millennials, Generation X-ers and Baby Boomers in the context of the UAE higher education.